An effective ISDPR rumor propagation model on complex networks - Jing, Wu; Kang, Haiyan (International journal of intelligent systems, 2022)
Rumor in networks is harmful, it can lead to social unrest, endanger public security, and do harm to the public interest. Therefore, it is very important to study the regularity of information spreading in the network. For the problem that traditional rumor propagation model did not take into account the influence of fact spreading and punishment mechanism, combined with network structure and game theory, propose an effective ISDPR rumor propagation model. First, we analyze the model, calculate the basic reproductive number and the equilibrium points and prove the stability of the equilibrium points to explain the rationality of the model. Then, based on game theory, a new state transition function is designed for nodes, and an effective ISDPR model on complex networks is proposed. Finally, experiments are performed in WS small world network, BA scale‐free network and real networks to investigate the influence of different initial conditions on rumor spreading, and the experimental results show the correctness and effectiveness of the model.